Increased prevalence of small airways dysfunction in patients with systemic sclerosis as determined by impulse oscillometry. (22nd August 2019) - Bonifazi, Martina; Sverzellati, Nicola; Negri, Eva; Pomponio, Giovanni; Seletti, Valeria; Bonini, Matteo; Fraticelli, Paolo; Paolini, Luca; Mattioli, Massimo; Franchi, Matteo; Tramacere, Irene; Poletti, Venerino; et al.
Abstract: Objectives: The prevalence and clinical implications of small airways involvement in SSc are still to be fully elucidated. The goal of the present work is to assess the prevalence of small airways dysfunction by impulse oscillometry and to determine whether it correlates with selected disease-related features and respiratory-related quality of life. Methods: Ninety-four SSc patients and 93 healthy controls were studied by impulse oscillometry measurements. Small airways dysfunction was defined as the difference between resistance at low frequency, i.e. 5 Hz, and resistance at high frequency, i.e. 20 Hz, termed 'R5-R20', ⩾0.07 kPa/l/s. The St George's Respiratory Questionnaire was used to measure health impairment in SSc patients. Radiological features of small airways disease and parenchymal abnormalities on high resolution CT chest scans were jointly assessed by two thoracic radiologists. Results: Small airways dysfunction was present in 21.5% of the SSc patient cohort, with a prevalence almost 5-fold higher compared with controls, and it was significantly associated with worse respiratory-related quality of life. Radiological features consistent with small airways abnormalities were detected in 25% of SSc patients, mostly in the absence of interstitial lung changes. Combining functional and radiological evaluations, one-third of the SSc cohort showed at least one feature of small airways involvement, which was associated with the lcSSc phenotype and with longer disease duration. Conclusion: The current study strengthens the hypothesis that small airway dysfunction might be a feature of SSc-related lung involvement, providing the first data on its significant impact on respiratory-related quality of life. A full assessment of lung function in SSc patients should include impulse oscillometry as a complementary technique, due to potential clinical and therapeutic implications.